On graph models in knowledge engineering - Ligęza, Antoni; Adrian, Weronika Teresa; Adrian, Marek; Kluza, Krzysztof; Jobczyk, Krystian; Wiśniewski, Piotr; Ślażyński, Mateusz; Jemioło, Paweł; Sepioło, Dominik; Stachura-Terlecka, Bernadetta; Zaremba, Mateusz; Szymkowski, Mateusz; et al. (Wydawnictwa AGH, 2023)
The paper presents selected applications of graph models in knowledge engineering. Starting from the basic definition of a graph as a set of nodes connected by edges, the article presents possible extensions of this concept aimed at increasing the power of expression and the ability to process knowledge. In particular, the work focuses on selected applications of graph models in research areas explored by the members of the KRaKEn research team.

W pracy przedstawiono wybrane zastosowania grafowych modeli w inżynierii wiedzy. Wychodząc od bazowej definicji grafu jako zbioru węzłów połączonych krawędziami, zaprezentowano możliwe rozszerzenia tego pojęcia ukierunkowane na zwiększenie siły ekspresji i możliwości przetwarzania wiedzy. W szczególności praca koncentruje się na wybranych zastosowaniach modeli grafowych w obszarach eksplorowanych przez członków grupy badawczej KRaKEn.
Rzecz o modelach grafowych w inżynierii wiedzy
Nauka – Technika – Technologia : seria wydawnicza AGH. Tom 8
Keywords: graph; graph models; multigraphs; hypergraphs; causal graphs; knowledge graphs; BPMN; DMN; constraint representation graphs; graf; modele grafowe; multigrafy; hipergrafy; grafy przyczynowo-skutkowe; grafy wiedzy; BPMN; DMN; grafy reprezentacji ograniczeń